2014
DOI: 10.1139/cjfas-2013-0274
|View full text |Cite
|
Sign up to set email alerts
|

Influence of sex, migration distance, and latitude on life history expression in steelhead and rainbow trout (Oncorhynchus mykiss)

Abstract: In partially migratory species, such as Oncorhynchus mykiss, the emergence of life history phenotypes is often attributed to fitness trade-offs associated with growth and survival. Fitness trade-offs can be linked to reproductive tactics that vary between the sexes, as well as the influence of environmental conditions. We found that O. mykiss outmigrants are more likely to be female in nine populations throughout western North America (grand mean 65% female), in support of the hypothesis that anadromy is more … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
66
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 54 publications
(71 citation statements)
references
References 49 publications
(62 reference statements)
5
66
0
Order By: Relevance
“…Larger females also attract more potential mates, acquire high-quality spawning sites, mobilize larger substrate, and dig deeper nests (Fleming and Reynolds 2004;Steen and Quinn 1999). Consequently, female salmonines are more frequently anadromous (Morita and Nagasawa 2010;Ohms et al 2014) and on average mature at larger sizes and older ages than males (Hendry et al 2004;Jonsson and Jonsson 1993).…”
Section: Fitness Trade-offs In Partially Migratory Salmoninesmentioning
confidence: 99%
See 2 more Smart Citations
“…Larger females also attract more potential mates, acquire high-quality spawning sites, mobilize larger substrate, and dig deeper nests (Fleming and Reynolds 2004;Steen and Quinn 1999). Consequently, female salmonines are more frequently anadromous (Morita and Nagasawa 2010;Ohms et al 2014) and on average mature at larger sizes and older ages than males (Hendry et al 2004;Jonsson and Jonsson 1993).…”
Section: Fitness Trade-offs In Partially Migratory Salmoninesmentioning
confidence: 99%
“…While migration distance is often considered an important factor affecting salmonine life history patterns (Hendry et al 2004), we found only one study that directly assessed migration distance on anadromy across populations at varying distances from the ocean. In that study, Ohms et al (2014) hypothesized that residency in male O. mykiss would be more common when migration distance was greater, in which case the sex ratios of outmigrating smolts should be female-biased (Table 4). However, analysis of data from eight North American O. mykiss populations with migration distances ranging from ϳ1 to 1200 km found no association between Fig.…”
Section: Freshwater Migration Challengesmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have found that the sex ratio of juvenile steelhead approximates 50:50 (male : female) prior to migration (Hausch and Melnychuk ; Ohms et al. ; Thompson et al. ), while out‐migrating smolts are frequently female‐biased (Peven et al.…”
Section: Discussionmentioning
confidence: 99%
“…; Ohms et al. ) in steelhead and other salmonid species (Jonsson and Jonsson ; Jonsson et al. ; Hendry et al.…”
Section: Discussionmentioning
confidence: 99%